miRNA, lncRNA and circRNA: Targeted Molecules Full of Therapeutic Prospects in the Development of Diabetic Retinopathy - Chang, Xingyu; Zhu, Guomao; Cai, Zongyan; Wang, Yaqi; Lian, Rongna; Tang, Xulei; Ma, Chengxu; Fu, Songbo (Frontiers in Endocrinology, 2021)
Diabetic retinopathy (DR) is a common diabetic complication and the main cause of blindness worldwide, which seriously affects the quality of life of patients. Studies have shown that noncoding RNA (ncRNA) has distinct differentiated expression in DR and plays an important role in the occurrence and development of DR. ncRNAs represented by microRNAs (miRNAs), lncRNAs (lncRNAs), and circRNAs (circRNAs) have been shown to be widely involved in the regulation of gene expression and affect multiple biological processes of retinopathy. This article will review three RNAs related to the occurrence and development of DR on the basis of previous studies (especially their effects on retinal microangiopathy, retinal pigment epithelial cells, and retinal nerve cells) and discuss their underlying mechanisms and connections. Overall, this review will help us better understand the role of ncRNAs in the occurrence and development of DR and provide ideas for exploring potential therapeutic directions and targets.